A Review of the Composition of the Essential Oils and Biological Activities of Angelica Species - Kandasamy Sowndhararajan; Ponnuvel Deepa; Minju Kim; Se Jin Park; Songmun Kim (MDPI AG, 2017)
A number of Angelica species have been used in traditional systems of medicine to treat many ailments. Especially, essential oils (EOs) from the Angelica species have been used for the treatment of various health problems, including malaria, gynecological diseases, fever, anemia, and arthritis. EOs are complex mixtures of low molecular weight compounds, especially terpenoids and their oxygenated compounds. These components deliver specific fragrance and biological properties to essential oils. In this review, we summarized the chemical composition and biological activities of EOs from different species of Angelica. For this purpose, a literature search was carried out to obtain information about the EOs of Angelica species and their bioactivities from electronic databases such as PubMed, Science Direct, Wiley, Springer, ACS, Google, and other journal publications. There has been a lot of variation in the EO composition among different Angelica species. EOs from Angelica species were reported for different kinds of biological activities, such as antioxidant, anti-inflammatory, antimicrobial, immunotoxic, and insecticidal activities. The present review is an attempt to consolidate the available data for different Angelica species on the basis of major constituents in the EOs and their biological activities.